2019
DOI: 10.3390/ma12040595
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Film Based on Cellulose Acetate and Lignin-Rich Rice Straw Nanofibers

Abstract: Nanofibers isolated from unbleached neutral sulfite rice straw pulp were used to prepare transparent films without the need to modify the isolated rice straw nanofibers (RSNF). RSNF with loading from 1.25 to 10 wt.% were mixed with cellulose acetate (CA) solution in acetone and films were formed by casting. The films were characterized regarding their transparency and light transmittance, microstructure, mechanical properties, crystallinity, water contact angle, porosity, water vapor permeability, and thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In a previous publication, it has been shown that RSNF with high lignin content (~14 wt.%) could be isolated from rice straw xylanase-treated unbleached sulfite pulp with a width of ~14 ± 7 nm, as seen in Figure 1 [31]. Water in the isolated RSNF could be easily exchanged by filtration and simple washing using different non-aqueous aprotic solvent [34].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication, it has been shown that RSNF with high lignin content (~14 wt.%) could be isolated from rice straw xylanase-treated unbleached sulfite pulp with a width of ~14 ± 7 nm, as seen in Figure 1 [31]. Water in the isolated RSNF could be easily exchanged by filtration and simple washing using different non-aqueous aprotic solvent [34].…”
Section: Resultsmentioning
confidence: 99%
“…This ester is usually obtained by cellulose esterification with acetic acid and acetic anhydride in the presence of sulfuric acid, followed by partial hydrolysis of the triacetate ester. Cellulose acetate, unlike cellulose has an excellent solubility in various organic solvents, having also a satisfactory mechanical strength, which allows its processing into films, membranes, or fibers [ 21 , 22 ]. Taking advantage of these features of cellulose acetate, it can be used for development of sustainable and environmentally friendly materials for the food packaging industry.…”
Section: Introductionmentioning
confidence: 99%
“…CNFs and CNCs hydrophilicity and easily functionalizable surface are important features to retard and/or prevent fouling [224]. Membranes prepared by CNF incorporation into composites with a polymer matrix, such as cellulose acetate [225,226], polyethylene oxide [227], polyvinyl alcohol [228,229] polypyrrole [230], poly (ether sulfone), and polyhydroxybutyrate [231], have been tested for the removal of heavy metals. Moreover, composite membranes obtained by incorporating zeolitic imidazolate framework-8 (ZIF-8) in CNFs show high durability for the selective removal of 99% of cationic dyes from anionic and cationic dye mixtures (Figure 12).…”
Section: Membrane Materials For Wastewater Treatmentmentioning
confidence: 99%